Examining the Impact of Macroeconomic Factors and Non-Performing Loans on Banking Sector Profitability: A Panel Data Analysis for East Africa Using the ARDL Model - Mwanjilinji, Emmanuel Ezekiel; Huang, Fei-Ming (International Journal of Business, Management and Economics, 2025)
Can the profitability of banks in East Africa withstand the dual challenges of non-performing loans (NPLs) and volatile macroeconomic conditions? This study examines the interplay between NPLs, macroeconomic factors (money supply, GDP, inflation) and banking sector performance in Tanzania, Kenya, and Uganda over the period 2000-2022. Using panel data and the Autoregressive Distributed Lag (ARDL) model, we uncover nuanced relationships between these variables. Cointegration analysis confirms a long-term equilibrium relationship, while the Pooled Mean Group (PMG) regression results reveal a rapid adjustment to equilibrium. The findings highlight that NPLs exert a significant negative long-term impact on profitability metrics; Return on Assets (ROA) and Return on Equity (ROE), underscoring the importance of robust credit risk management. Interestingly, short-term dynamics suggest that inflation can temporarily enhance profitability, while NPLs immediately diminish ROE. These insights provide valuable guidance for policymakers and banking executives seeking to bolster the resilience and growth of the East African banking sector. Future research should broaden this analysis to include political and global economic variables for a more comprehensive understanding of banking profitability in emerging markets